Pengaruh Current Ratio, Net Profit Margin Dan Price Earning Ratio Terhadap Return Saham Pada Perusahaan Subsektor Otomotif dan Komponen yang Terdaftar Di Bursa Efek Indonesia (BEI) - Andri Adidi; Reva Maria Valianti (Universitas PGRI Palembang, 2019)
This study aims to determine the effect of current ratio, net profit margin and price earning share on stock returns of the automotive and component sub-sector companies. The sample was selected as many as 8 companies from 12 companies listed on the IDX. The data analysis technique uses a multiple linear regression analysis model after going through the testing phase of the model which is the classic assumption which consists of data normality test, autocorrelation test, multicollinearity test and heteroscedasticity test. Further testing of the F test hypothesis and t test is carried out. The test results show that the current ratio, net profit margin and price earning share obtained a value of 0.097 which means that simultaneously there is no significant effect on the independent variable on the dependent variable. The results of the t test for the current ratio variable obtained a value of 0.962> 0.05, the variable net profit margin obtained a value of 0.223> 0.05 means that CR and NPM have no significant effect on stock returns. Price earning share variable obtained value of 0.044> 0.05 means that there is a significant effect on stock returns. Keywords : Current Ratio, Net Profit Margin, Price Earning Ratio and Stock ReturnPenelitian ini bertujuan untuk mengetahui pengaruh current ratio, net profit margin dan price earning share terhadap pengembalian saham perusahaan subsektor notomotif dan komponen. Sampel terpilih sebanyak 8 perusahaan dari 12 perusahaan yang terdaftar di BEI. Teknik analisis data menggunakan model analisis regresi linear berganda setelah melalui tahap pengujian model yaitu asumsi klasik yang terdiri dari uji normalitas data, uji autokorelasi, uji multikolinearitas dan uji heterokedastisitas. Selanjutnya dilakukan pengujian hipotesis uji F dan uji t. Hasil pengujian menunjukkan hasil bahwa current ratio, net profit margin dan price earning share diperoleh nilai sebesar 0,097 artinya secara simultan tidak terdapat pengaruh signifikan terhadap variabel independen terhadap variabel dependen. Hasil uji t untuk variabel current ratio diperoleh nilai sebesar 0,962 > 0,05, variabel net profit margin diperoleh nilai sebesar 0,223 > 0,05 artinya CR dan NPM tidak berpengaruh signifikan terhadap pengembalian saham. Variabel Price earning share diperoleh nilai sebesar 0,044 > 0,05 artinya terdapat pengaruh signifikan terhadap pengembalian saham. Kata Kunci : Current Ratio, Net Profit Margin, Price Earning Ratio dan Return Saham